Meningkatkan Daya Saing UMKM Kartini di Pasar Internasional - Ramadhani, Yesa; Budiarti, Anindhyta; Kurnia, Kurnia; Subardjo, Anang (STIE Miftahul Huda, 2025)
Paguyuban Kartini Mandiri is the ability of its MSME members to provide training to the government and private sector, and facilitate its members to manage IUMK, NIB, NPWP, and PIRT independently. The Bojonegoro Regency Government has expressed support for the development of MSMEs, both through training, mentoring, and access to capital. E-marketing is a made of entry option that is considered effective and efficient, especially for digital products, such as software, videos, music, and the like. All the high developments in information and communication technology, people use information and communication technology to transact, make sales, purchases through e-commerce. The obstacles for MSME actors in Paguyupan Kartini Mandiri Bojonegoro City are Access to capital, many MSMEs have difficulty getting access to adequate financing, especially from formal banking institutions. Limited collateral and lack of a neat financial track record are obstacles for MSMEs to get loans with low interest rates. Lack of digital knowledge and skills, not all MSMEs are familiar with digital platforms and online marketing strategies.